Determinants of the sustainability and growth of micro and small enterprises (MSEs) in Ethiopia: Literature review - Beza Muche Teka (Journal of Innovation and Entrepreneurship, 2022)
The role of micro and small enterprises (MSEs) has been recognized in Ethiopia at the strategic and policy levels. They are considered as a way to create jobs, alleviate poverty, ensure food security, and promote private sector development. Despite several government programs and support schemes aimed at empowering MSEs to be more competitive and sustainable, they continue to fail at alarming rates. Previous studies revealed that the failure rate of MSEs in developing countries like Ethiopia is higher than in developed countries due to a variety of internal and external factors. Thus, the objective of this study was to identify the major factors that commonly affect the sustainability and growth of MSEs in Ethiopia through systematic literature review. In order to achieve the objective of the study; published previous research works (journal articles) in the manufacturing and service sector from 2006 to 2021 were used. The findings from different empirical studies revealed that financial factors, marketing factors, political-legal variables, lack of adequate infrastructure, technological factors and manager or owner personal characteristics are the major factors that commonly determine the sustainability and growth of MSEs in Ethiopia. Finally, the study suggested that government, non-governmental organizations (NGOs), and financial institutions should give great attention towards the sustainability and growth of MSEs in Ethiopia.
Keywords: 650; Financial factors; Infrastructure factors; Manager or owner personal characteristics; Marketing factors; political-legal variables; Sustainability and growth